2006
DOI: 10.1115/1.2335857
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Modeling of Process Damping in Peripheral Milling

Abstract: This paper extends analytical modeling of the milling process to include process damping effects. Two cutting mechanisms (shearing and plowing mechanisms) and two process damping effects (directional and magnitude effects) are included. The directional effect is related to vibration energy dissipation due to directional variation of cutter∕workpiece relative motion. The magnitude effect is associated with change in force magnitude due to variation of rake angle and clearance angle. Process damping is summarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…More recently Huang and Wang [27] proposed a semi-analytical model that considered the dynamically changing angles of the ploughing and shearing forces during cutting. A matrix of empirical coefficients was used to characterize the process-damping forces, which were assumed to be functions of the direction of relative motion between tool and workpiece.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently Huang and Wang [27] proposed a semi-analytical model that considered the dynamically changing angles of the ploughing and shearing forces during cutting. A matrix of empirical coefficients was used to characterize the process-damping forces, which were assumed to be functions of the direction of relative motion between tool and workpiece.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To summarize, there have been a number of attempts to model the forces that occur during milling at low spindle speeds, based upon the original conceptual theory proposed over 50 years ago. Some of these models have focused on the forces arising due to physical interference between the tool and workpiece, whilst other work has investigated the consequence of a changing relief and rake angle on the dynamic cutting forces [27]. Perhaps the most comprehensive work involving the former method is that described in the PhD thesis of Ranganath (see Ranganath et al [24]).…”
Section: Literature Reviewmentioning
confidence: 99%
“…To understand the process damping, pioneers have already done some excellent works trying to explain how process damping generates and affects the machining stability. 714 Moreover, process damping models for specific issues, such as 2-degree-of-freedom (DOF) regenerative chatter, 15 different tool geometries, 16 influence of feed rate on process damping, 17 micro-milling operations, 18 mode coupling, 19 and thin-wall milling, 20 were also discussed. To identify the coefficients related to process damping, several methods were established, including fast tool servo device, 21 energy dissipation principle, 22 inverse stability analysis method, 23,24 operational modal analysis method, 25,26 turning process excitation method, 27 and the generalized method with static milling forces.…”
Section: Introductionmentioning
confidence: 99%
“…Many prior process damping studies have identified it as energy dissipation due to interference between the cutting tool clearance face and machined surface during relative vibrations between the two [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Because process damping enables increased material removal rates at low cutting speeds, it is an important consideration when modeling machining operations for hard-to-machine materials.…”
Section: Introductionmentioning
confidence: 99%